(NH4)Bi2(IO3)2F5: An Unusual Ammonium‐Containing Metal Iodate Fluoride Showing Strong Second Harmonic Generation Response and Thermochromic Behavior. Issue 13 (9th January 2020) - Fan, Huixin; Lin, Chensheng; Chen, Kaichuang; Peng, Guang; Li, Bingxuan; Zhang, Ge; Long, Xifa; Ye, Ning
Abstract: An ammonium‐containing metal iodate fluoride compound, (NH4 )Bi2 (IO3 )2 F5, featuring a two‐dimensional double‐layered framework constructed by [BiO2 F5 ] 6− and [BiO4 F4 ] 9− polyhedra, as well as [IO3 ] − groups, was successfully synthesized. The well‐ordered alignment of these SHG‐active units leads to an extraordinary strong SHG response of 9.2 times that of KDP. Moreover, this compound possesses a large birefringence (Δ n =0.0690 at 589.3 nm), a wide energy band gap ( E g =3.88 eV), and a high laser damage threshold (LDT; 40.2×AgGaS2 ). In particular, thermochromic behavior was observed for the first time in this type of compound. Such multifunctional crystals will expand the application of nonlinear optical materials. Abstract : Multitalented : The introduction of ammonium into a bismuth iodate fluoride to give (NH4 )Bi2 (IO3 )2 F5 led to a crystal showing a subtle balance of a strong second harmonic generation effect, large birefringence, and a high laser damage threshold. In particular, the crystal exhibited unusual thermochromism. Such multifunctional behavior expands the potential of nonlinear optical materials (see picture).